`DINAMIKA KONFLIK DALAM STRUKTUR NARATIF PADA NOVEL CANTIK ITU LUKA KARYA EKA KURNIAWAN - Pramudita, Dea Restu; Dzarna, Dzarna; Vardani, Eka Nova Ali; Amalia , Fitri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research discusses the dynamics of conflict in the narrative structure in Eka Kurniawan's novel titled Cantik itu Luka. The novel combines magical realism with Indonesian history, depicting various social and political events in the lives of its characters. The main component of the story is the conflict, both internal and external, which shows the emotional and moral struggles of the characters. According to Elok et al. (2019) Emotion is a form of state or feeling that describes a person experiencing various kinds of events. To study conflict patterns and how conflicts affect the storyline, this study uses a qualitative narrative approach. Internal conflicts, such as Dewi Ayu's trauma, give psychological depth to the characters. On the contrary, external conflicts, such as Dewi Ayu's feud with the Camp Commander, show the struggle of the characters against oppressive outside forces. In addition, this study discusses how conflicts are explained through a narrative approach. Internal focal points allow for a deeper understanding of the character's thoughts and feelings, as seen in the prayer of Dewi Ayu who asks for her child to be born in bad circumstances to protect her from difficulties. The dynamics of the relationship between the characters and their social environment are also depicted through a direct dialogue approach and an omniscient third-person perspective. The results of this study show that the narrative structure of the novel combines internal and external conflicts regularly, creating a complex and deep storyline. Internal conflicts, such as moral dilemmas and character fears, often determine the understanding of their motivations. External conflicts, on the other hand, connect the characters to broader social and political issues, providing a historical context that supports the novel's themes. Therefore, Cantik itu Luka reflects Indonesia's history, society, and social reality. The research also aids in literary research, especially on the ways in which conflict can be used to create complex narratives. The study also shows that narrative techniques not only serve as a way to tell a story, but also as a way to reveal the social dynamics and psychological depths that affect characters. This research offers a new way to look at the narrative structure of Indonesian novels.